Analysis of Water Contaminated Engine Oil in Engine Generator Set - Wilarso Wilarso; Firmansyah Azharul; Che Wan Mohd Noor; Dan Mugisidi (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
This case study was conducted in a manufacturing company that experienced a breakdown in a power generator set. A standard investigation was carried out by opening the crankcase cover and checking the dipstick. The results of the visual inspection showed that the engine oil was contaminated with water. Therefore, this study was conducted to further analyze the causes of oil contaminated with water in the unit being handled using fault tree analysis (FTA). As a result, cracks were found in the cylinder liner due to pitting on the outer liner with a pitting depth of more than 2 mm. In our analysis, pitting is formed due to the presence of air bubbles in the cooling system. Based on FTA, the formation of air bubbles is caused by the quality of the coolant. We also found that the coolant used was not added with any additives.